Peri-operative troponin I concentration as a marker of long-term postoperative adverse cardiac outcomes--a study in high-risk surgical patients. - Higham, H; Sear, J; Sear, Y; Kemp, M; Hooper, R; Foex, P (2004)
We have previously demonstrated that the peri-operative measurement of increased serum concentrations of the cardiac markers troponins I and T and creatine kinase-MB can be predictors of major cardiovascular outcomes (including cardiac death) at 3 months after surgery. In the present study, we have followed the postoperative course of 157 patients undergoing major vascular surgery or major joint arthroplasty to 1 year using a patient questionnaire, general practitioner follow-up and case-notes review. Increased postoperative marker concentrations were defined as values greater than the upper reference limit. Increases in troponin I and troponin T concentrations, as well as a single elevated creatine kinase-MB and two successively elevated creatine kinase-MB concentrations were measured in 12, 13, 33 and 15 patients respectively. Thirty-nine major adverse cardiac outcomes were recorded (cardiac death, myocardial ischaemia, congestive cardiac failure, unstable angina, cerebrovascular accident and major arrhythmias needing active treatment). There was no association between increases in any of these cardiac markers and cardiac death to 1 year. However, increases in troponin I and both a single elevated creatine kinase-MB and two successively elevated creatine kinase-MB concentrations were associated with an increased incidence of major cardiac outcomes, including cardiac death, to 1 year (odds ratio [95% confidence intervals] = 4.19 [1.16-14.87], 3.97 [1.65-9.44] and 5.19 [1.60-16.22], respectively).